PENGARUH CAMPURAN AIR LIMBAH (AIR SELOKAN) TERHADAP KUAT TEKAN BETON f’c 14.5 Mpa (K-175) - Rasio Hepiyanto; Dwi Kartikasari (Kadiri University, 2018)
In improving technological progress, the use of concrete as a building is very popular in Indonesia. Because it can utilize materials that are easily obtained such as crushed stone, gravel, sand, cement and water at a relatively cheap price. On a daily use basis often found in housing construction project workers who use waste water (Sewer Water) for concrete processing. This of course requires a closer inspection of the quality of the concrete produced. The data analysis method begins with the investigation of cement materials, coarse and fine aggregates. Mixing concrete using clean water (PDAM) as a reference and waste water (Sewer Water) from the Unisla flat building. From the analysis that has been done, it is obtained the results of the compressive strength test of concrete at the age of 7, 14 and 28 days by mixing clean water of 13.68 MPa, 18.51 MPa, 21.04 MPa, while the results of the concrete compressive strength test at ages 7, 14 and 28 days by mixing Wastewater (Sewer Water) at 9.99 MPa, 13.35 MPa and 15.36 MPa. Keywords : Wastewater, Concrete, Compressive Strength Dalam meningkatkan kemajuan teknologi, pemakaian beton sebagai bangunan sangat popular di indonesia. Karena bisa memanfaatkan bahan yang mudah diperoleh seperti batu pecah, batu kerikil, pasir, semen dan air dengan harga yang relatif murah.Pada penggunaan sehari-hari sering dijumpai pada pekerja proyek pembangunan rumah tinggal yang menggunakan air limbah (Air Selokan) untuk pengerjaan pembetonan. Hal ini tentunya memerlukan pemeriksaan yang lebih teliti terhadap mutu beton yang dihasilkan. Metode analisa data dimulai dengan penyelidikan bahan semen, agregat kasar dan halus. Pencampuran beton menggunakan air bersih (PDAM) sebagai acuan dan air limbah (Air Selokan) dari gedung rusunawa Unisla. Dari analisa yang telah dilakukan didapat hasil pengujian kuat tekan beton pada umur 7, 14 dan 28 hari dengan pencampuran air bersih sebesar 13,68 Mpa, 18,51 Mpa, 21,04 Mpa, sedangkan hasil pengujian kuat tekan beton pada umur 7, 14 dan 28 hari dengan pencampuran Air Limbah (Air Selokan) sebesar 9,99 MPa, 13,35 MPa, dan 15,36 MPa. Kata Kunci : Air Limbah, Beton, Kuat Tekan